2023
DOI: 10.1111/ggi.14646
|View full text |Cite
|
Sign up to set email alerts
|

Statin use impairs muscle strength recovery in post‐stroke patients with sarcopenia

Abstract: AimThe effects of statins on muscle health are not well established. Therefore, this study investigated the impact of statin use on muscle strength and mass recovery in patients with sarcopenia after stroke.MethodsThis retrospective cohort study included stroke patients with sarcopenia hospitalized between 2015 and 2021 at a post‐acute rehabilitation hospital. Sarcopenia was diagnosed using handgrip strength and skeletal muscle mass index measured using bioelectrical impedance analysis according to the 2019 cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Several observational studies have shown that statins reduce physical activity, 8 muscle strength, 9,10 and delay muscle recovery after cerebrovascular injury. 11 However, there are several conflicting reports that statins do not affect skeletal muscle mass 12 and that statins reduce the development of sarcopenia and enhance physical function. [13][14][15] In the only intervention study targeting the effects of statins on skeletal muscle (420 healthy subjects followed for 6 months for exercise capacity and muscle strength after 80 mg atorvastatin or placebo), during the observation period, 9.4% in the statin group (4.6% in the placebo group, P = 0.05) developed myalgia and a mild elevation of serum CK was observed in the statin group (mean increase since enrollment 20.8 AE 141.1 U/L).…”
Section: Hydroxymethylglutaryl-coa Reductase Inhibitors (Statins)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies have shown that statins reduce physical activity, 8 muscle strength, 9,10 and delay muscle recovery after cerebrovascular injury. 11 However, there are several conflicting reports that statins do not affect skeletal muscle mass 12 and that statins reduce the development of sarcopenia and enhance physical function. [13][14][15] In the only intervention study targeting the effects of statins on skeletal muscle (420 healthy subjects followed for 6 months for exercise capacity and muscle strength after 80 mg atorvastatin or placebo), during the observation period, 9.4% in the statin group (4.6% in the placebo group, P = 0.05) developed myalgia and a mild elevation of serum CK was observed in the statin group (mean increase since enrollment 20.8 AE 141.1 U/L).…”
Section: Hydroxymethylglutaryl-coa Reductase Inhibitors (Statins)mentioning
confidence: 99%
“…Several observational studies have shown that statins reduce physical activity, 8 muscle strength, 9,10 and delay muscle recovery after cerebrovascular injury 11 . However, there are several conflicting reports that statins do not affect skeletal muscle mass 12 and that statins reduce the development of sarcopenia and enhance physical function 13–15 .…”
Section: Drugs That Cause a Certain Frequency Of Sarcopenia Or Myopathymentioning
confidence: 99%
“…Sarcopenia is a progressive and generalized skeletal muscle disorder characterized by accelerated loss of muscle strength, mass and function, leading to an increased risk of falls and hospitalization, particularly among the elderly population. A previous retrospective cohort study involving 586 sarcopenia patients reported an adverse association between statin use and recovery of muscle strength [ 9 ]. However, there exists inconsistency in the current clinical evidence, as another cross-sectional study including 136 heart failure patients found that statin use was associated with a reduced likelihood of developing sarcopenia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%